Analysis of Manhaj Ibn Hibban in Writing the Book of Al-Siqat - Kuswandi, Yadi; Dadah, Dadah; Muhammad Al Mighwar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper discusses Ibn Hibban's manhaj which is found in the Book of Al-Siqat. This book has become a reference for scholars and experts in hadith science to determine the quality of hadith narrators. Ibnu Hibban has tried to collect data about hadith narrators. In this book, we can see the comments and notes of hadith critics regarding a narrator, namely their acceptance or rejection of the narration. Next, the degree and status of the hadith narrated is determined.